Faktor Pengetahuan, Sikap, dan Dukungan Suami yang Berhubungan dengan Perilaku Wanita Usia Subur dalam Pemeriksaan IVA Tes di Desa Sukamanah, Kabupaten Bekasi - Yohana Puspitarani; Rohani Siregar; Ika Kania Fatdo Wardani; Herlina Simanjuntak (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
Cervical cancer is one of the leading causes of death among women and is largely caused by Human Papilloma Virus (HPV) infection. Visual Inspection with Acetic Acid (VIA) is a simple, effective, and recommended method for early detection to reduce morbidity and mortality rates from cervical cancer. However, VIA screening coverage in Indonesia remains low, including in the working area of Sukatani Health Center. This study aimed to identify indicators associated with the behavior of women of reproductive age (WRA) in undergoing VIA screening in Sukamanah Village. This research employed a quantitative method with a cross-sectional design, involving 82 WRA respondents selected through consecutive sampling. Independent variables included education, knowledge, attitude, information sources, and spousal support. Data were collected using questionnaires and analyzed with the chi-square test. The results showed that 61% of respondents had never undergone a VIA test. Significant associations were found between VIA screening behavior and knowledge (p=0.003), attitude (p=0.021), and spousal support (p=0.003). Meanwhile, education (p=0.073) and sources of information (p=0.075) were not significantly associated. These findings highlight that improving knowledge, fostering positive attitudes, and strengthening spousal support are key strategies to increase WRA participation in VIA screening for early cervical cancer detection.